A narrative review and meta-analysis of service interaction quality: new research directions and implications. Issue 1 (9th February 2015) - Ranjan, Kumar Rakesh; Sugathan, Praveen; Rossmann, Alexander
Abstract : Purpose: – This paper aims to conceptualize and empirically test the determinants of service interaction quality (SIQ) as attitude, behavior and expertise of a service provider (SP). Further, the individual and simultaneous effects of SIQ and its dimensions on important marketing outcomes are tested. Design/methodology/approach: – The narrative review of extant research helps formulate a conceptual model of SIQ, which is investigated using the univariate and multivariate meta-analysis. Findings: – There are interdependencies between drivers of SIQ that underlines the need to conceptualize service interaction as a dyadic phenomenon; use contemporary multilevel models, dyadic models, non-linear structural equation modeling and process studies; and study new and diverse services contexts. Meta-analysis illustrates the relative importance of the three drivers of SIQ and, in turn, their impact on consumer satisfaction and loyalty. Research limitations/implications: – The meta-analysis is based on existing research, which, unfortunately, has not examined critical services or exigency situations where SIQ is of paramount importance. Future research will be tasked with diversifying to several important domains where SIQ is a critical aspect of perceived service quality. Practical implications: – This study emphasizes that, although the expertise of an SP is important, firms would be surprised to learn that the attitude and behavior of their employees are equally important antecedents. In fact, there is a delicate balance that needs to be found; otherwise, attitudinal factors can have an overall counterproductive effect on consumer satisfaction. Originality/value: – This paper provides an empirical synthesis of SIQ and opens up interesting areas for further research.